Rebalancing for Long-Term Investors: Why it Pays to Do Less - DRIESSEN, JOOST; KUIPER, IVO (Bankers, Markets & Investors, 2019)
In this study we show that the rebalancing frequency of a multi-asset portfolio has only limited impact on the utility of a long-term passive investor. Although continuous rebalancing is optimal, the loss of a suboptimal strategy corresponds to up to only 30 basis points of the initial wealth of the investor, assuming market returns are unpredictable and transaction costs can be ignored. Our results suggest that reducing transaction costs clearly outweighs the benefit of frequent rebalancing. When we study a setting where asset returns are predictable, we find that a longterm investor that ignores this predictability underestimates the benefit of less frequent rebalancing. In this setting, limiting the rebalancing frequency to once every quarter results in significant higher utility, even without transaction costs.